Analysis of Balanced Diet Index Score with Fasting Blood Glucose in Adult in SDN X Sidoarjo: Analisis Skor Indeks Gizi Seimbang dengan Nilai Glukosa Darah Puasa pada Usia Dewasa di SDN X Sidoarjo - Nuriannisa, Farah; Yuliani, Kartika; Nidianti, Ersalina; Rizkiyah, Mubarokator; Santoso, Rizma Defva (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Adherence to Pedoman Gizi Seimbang is one of important part of non-communicable diseases prevention. Diet quality and quantity need to be assessed, thus it can detect the risk of non-communicable diseases. Healthy Eating Index (HEI) has been used in many previous studies as an indicator to examine the relationship between diet quality and disease biomarker, like fasting blood glucose (FBG). In Indonesia, the HEI has been modified to Indeks Gizi Seimbang (IGS). However there is no study that examine the relationship between IGS score and biomarker such as FBG yet. This study objective was to analyze the correlation between IGS score and FBG in adult in SDN X Sidoarjo. A cross sectional study design with 30 respondents. IGS4-105 score was measured by 2-days repeated 24h-recall, while FBG by using Glucostick method. Mann Whitney and Spearman test were performed to analyze the study results. The respondents' vegetable intake was relatively low (55.4 grams/day), while the intake of total fat (32.6%-e), saturated fat (16.7%-e), and added sugar (6.8%-e) were excessive. The intake of vegetables and non-dairy animal foods was significantly different between normal FBG group and high FBG group (respectively p value: 0.046, 0.011). The mean score of IGS4-105 was 52.3. There was no significant relationship between the IGS4-105 score and the FBG, but a positive relationship was found between the IGS score for animal foods and the FBG (r = 0.38; p = 0.04). A higher FBG was found in the group with a higher animal food IGS score.